A receiver's approach to family business brands: Exploring individual associations with the term "family firm". Issue 2 (9th July 2018) - Botero, Isabel C.; Astrachan, Claudia Binz; Calabrò, Andrea
Abstract : Purpose: Although prior research has indicated that ownership characteristics of a firm can influence how organizations are perceived, there is a gap in our understanding of the general associations that individuals have with the term "family firm." Some argue that promoting a firm as family-owned can result in positive evaluations by stakeholders; others argue that it can result in negative perceptions about a firm. However, very few empirical projects have directly explored the associations that external stakeholders have with the term "family firm." The purpose of this paper is to explore the associations that individuals in Switzerland have with the term "family firm." Design/methodology/approach: A two-stage study is conducted in this paper. In Stage 1 ( n =138), the authors generated the list of associations that individuals had with the term "family firm." The authors then categorized these associations into seven categories. In Stage 2 ( n =321), the authors explored whether these associations were unique to family firms by asking participants in the "family firm" or the "publicly owned company" condition to assess which descriptors better represented the condition the characteristics of organizations in their conditions. Findings: The findings indicate that there are seven general descriptor categories associated with the term "family firm." These are: tradition and continuity, small and medium companies, trustworthiness, strong culture, corporate citizenship, professionalism, and career opportunities. The findings also indicate that individuals have different associations with the terms "family firm" and "publicly owned company." While the term "family firm" is primarily associated with traditional, small, and trustworthy companies, the term "publicly owned company" is often associated with companies that are profit-oriented, large, and thought to offer superior career opportunities. Theoretical and practical implications of these results are discussed. Originality/value: This study continues to build our understanding of branding in family firms by helping us connect the term "family firm" with the direct associations in the mind of the audience. This is important because it can help practitioners and researchers better understand under which conditions promoting family firms will have a positive influence on consumers.